A psychosocial assessment and management tool for children and youth in crisis. Issue 1 (28th March 2018) - Lee, Alison; Deevska, Mariana; Stillwell, Karly; Black, Tyler; Meckler, Garth; Park, David; Eslami, Ali; Doan, Quynh
Abstract : CLINICIAN'S CAPSULE : What is known about the topic? Emergency clinicians are not specifically trained to assess and manage mental health emergencies; thus, they have wide practice variation while determining disposition for children with mental health crises. What did this study ask?: What is the inter-user reliability of a new emergency psychosocial assessment and management guiding tool, HEARTSMAP, and the impact of implementing it in a pediatric emergency department? What did this study find?: The tool demonstrated strong inter-rater reliability between PED clinicians and was associated with high rates of outpatient resource connectivity. Why does this study matter to clinicians?: HEARTSMAP can provide emergency clinicians with reliable and comprehensive assessment and management strategies for youth presenting with mental health-related concerns ABSTRACT: Objectives: To evaluate the psychometric properties of HEARTSMAP, an emergency psychosocial assessment and management tool, and its impact on patient care and flow measures. Methods: We conducted the study in two phases: first validating the tool using extracted information from a retrospective cohort, then evaluating implementation on a prospective cohort of youth presenting with mental health complaints to a tertiary Pediatric Emergency Department (PED). In phase 1, six PED clinicians applied HEARTSMAP to extracted narratives and we calculated inter-rater agreement for referral recommendations using Cohen's Kappa and the sensitivity and specificity for identifying youth requiring psychiatric consultation and hospitalization. In phase 2, PED clinicians prospectively used HEARTSMAP and we assessed the impact of the tool's implementation on patient-related outcomes and Emergency department (ED) flow measures. Results: We found substantial agreement (κ=0.7) for cases requiring emergent psychiatric consultation and moderate agreement for cases requiring community urgent and non-urgent follow-up (κ=0.4 each). The sensitivity was 76% (95%CI: 63%, 90%) and specificity was 65% (95%CI: 55%, 71%) using retrospective cases. During pilot implementation, 62 patients received HEARTSMAP assessments: 46 (74%) of HEARTSMAP assessments triggered a recommendation for ED psychiatry assessment, 39 (63%) were evaluated by psychiatry and 13 (21%) were admitted. At follow-up, all patients with HEARTSMAP's triggered recommendations had accessed community resources. For those hospitalized for further psychiatric care at their index or return visit within 30 days, 100% were initially identified by HEARTSMAP at the index visit as requiring ED psychiatric consultation. Conclusions: HEARTSMAP has strong reliability, and when applied prospectively is a safe and effective management tool. RÉSUMÉ: Objectif: L'étude visait à estimer les propriétés psychométriques du test HEARTSMAP, un instrument d'évaluation psychosociale d'urgence et un outil de prise en charge, et son incidence sur les soins aux patients et les mesures de roulement des patients. Méthode: L'étude a été menée en deux étapes : la première consistait en la validation de l'instrument reposant sur des renseignements tirés d'une cohorte rétrospective de sujets; la seconde, en l'évaluation de la mise en œuvre de l'instrument dans une cohorte prospective de jeunes ayant consulté pour des troubles de santé mentale dans un service des urgences pédiatriques (SUP) rattaché à un établissement de soins tertiaires. Au cours de la première étape, six cliniciens au SUP ont appliqué l'instrument HEARTSMAP aux extraits de récits; de notre côté, nous avons calculé le degré de concordance interévaluateurs en ce qui concerne les recommandations de consultation à l'aide du coefficient kappa de Cohen, et nous avons procédé à des mesures de la sensibilité et de la spécificité afin de distinguer les jeunes qui avaient besoin d'une consultation en psychiatrie ou qui devaient être hospitalisés. Au cours de la deuxième étape, les cliniciens au SUP ont appliqué l'outil HEARTSMAP de manière prospective; de notre côté, nous avons évalué l'incidence de la mise en œuvre de l'instrument sur les résultats cliniques observés chez les patients et sur les mesures de roulement des patients au service des urgences (SU). Résultats: Il s'est dégagé de l'analyse une concordance importante (κ=0, 7) en ce qui concerne les consultations urgentes en psychiatrie et une concordance modérée en ce qui concerne les suivis urgents ou non urgents dans la collectivité (κ=0, 4 respectivement). Dans l'analyse rétrospective, la sensibilité atteignait 76 % (IC à 95 % : 63 %; 90 %) et la spécificité, 65 % (IC à 95 % : 55 %; 71 %). Durant l'étape de la mise en œuvre pilote, 62 patients ont été soumis à l'instrument d'évaluation HEARTSMAP; une évaluation en psychiatrie au SU a été recommandée dans 46 (74 %) cas; il y a eu une évaluation en psychiatrie dans 39 (63 %) cas et l'hospitalisation a été nécessaire dans 13 (21 %) cas. À la consultation de suivi, tous les patients chez qui le test HEARTSMAP s'était soldé par des recommandations ont eu accès à des ressources communautaires. Quant à ceux qui ont été hospitalisés pour recevoir davantage de soins spécialisés en psychiatrie au moment de la consultation de référence ou de la consultation de suivi dans les 30 jours suivants, ils avaient tous été reconnus au départ, au test HEARTSMAP, comme des patients ayant besoin d'une consultation en psychiatrie au SU au moment de la consultation initiale. Conclusion: Le test HEARTSMAP s'est révélé un instrument d'évaluation très fiable ainsi qu'un outil sûr et efficace de prise en charge dans les applications prospectives.